2015
DOI: 10.1002/ejhf.260
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical picture and risk prediction of short‐term mortality in cardiogenic shock

Abstract: NCT01374867.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
525
7
32

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 619 publications
(651 citation statements)
references
References 30 publications
18
525
7
32
Order By: Relevance
“…A contemporary registry has reported that as many as 81% of patients presenting with CS had an underlying acute coronary syndrome (ACS). 55 Thus, among patients with CS within the appropriate demographic or with risk factors for coronary artery disease, ACS should be the focus of initial diagnostic testing, and this testing should include an ECG within 10 minutes of presentation. 56 Although 5% to 12% of ACS cases are complicated by CS, this presentation is often associated with a large degree of at-risk myocardium.…”
Section: Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…A contemporary registry has reported that as many as 81% of patients presenting with CS had an underlying acute coronary syndrome (ACS). 55 Thus, among patients with CS within the appropriate demographic or with risk factors for coronary artery disease, ACS should be the focus of initial diagnostic testing, and this testing should include an ECG within 10 minutes of presentation. 56 Although 5% to 12% of ACS cases are complicated by CS, this presentation is often associated with a large degree of at-risk myocardium.…”
Section: Pathogenesismentioning
confidence: 99%
“…In the non-ACS CS population, a contemporary registry (limited to 42 patients with non-ACS CS) reported an in-hospital mortality rate of 24% and that non-ACS pathogenesis was independently associated with better survival. 55 …”
Section: Contemporary Outcomes Prognosis and Resource Use Trends Inmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these systems are more invasive and not available outside tertiary care centres. Although the most frequent cause of CS is acute coronary syndrome, non-ischaemic aetiology accounts for up to one-fifth of CS cases [7]. The haemodynamic needs may be different in non-ischaemic CS, where low output may be triggered by volume overload, versus AMI, where myocardial contractile reserve is acutely impaired.…”
Section: Introductionmentioning
confidence: 99%